Open city a novel - Cole, Teju 1975- (Random House Trade Paperbacks, 2012)
"A haunting novel about identity, dislocation, and history, Teju Cole's Open City is a profound work by an important new author who has much to say about our country and our world. Along the streets of Manhattan, a young Nigerian doctor named Julius wanders, reflecting on his relationships, his recent breakup with his girlfriend, his present, his past. He encounters people from different cultures and classes who will provide insight on his journey - which takes him to Brussels, to the Nigeria of his youth, and into the most unrecognizable facets of his own soul."
Cover: "PEN Hemingway winner"
Keywords: Identity (Psychology) / Fiction; Nigerians / New York (State) / New York / Fiction; Race / Fiction; Fiktionale Darstellung